Improving teaching and learning in physical education - Harvey Grout; Gareth Long (England, 2009)
Supports you in your initial teacher training programme and beyond, taking you through the wide range of issues that you need to consider in order to become a successful teacher and develop successful learners. This book looks at important aspects of physical education (PE) teaching and relates it directly to the PE lesson and how pupils learn
Keywords: Physical education and training- study and teaching; Physical education teachers